Exploring family change processes: a dynamic qualitative analysis of family trajectories, change and coordination in child protection cases - Melo, Ana Teixeira de (2017)
This paper reports an exploratory discovery-oriented study aimed at inspecting change processes and dynamics in families referred by the Courts and Child Protection Services for family assessment in the Integrated Family Assessment and Intervention Model (IFAIM; Melo & Alarcão, 2011, 2013) due to child neglect. The families received support for change during an assessment aimed at facilitating and exploring their potential for change. The parents reported, in quantitative diaries, their family’s experiences and changes inside and outside the sessions. We coded the data with a qualitative coding-scheme emergent from a preliminary qualitative exploration based on grounded theory methods and sensitizing concepts from Complexity Science and Dynamic Systems Theories. Core categories of Trajectories of States, Trajectories of Coordination and Influence and Other Coordination Effects emerged as relevant indicators to understand the families’ potential for change, describing basic dynamic change processes and contributing to understand therapeutic outcomes. We discuss the implications of the results and directions for future studies.